Binnenwanderungen seit der deutschen Einigung - Schlömer, Claus (Raumforschung und Raumordnung | Spatial Research and Planning, 2004)
With the opening of the inner-German boundaries in 1989, the unification of Germany and the following upheavals in numerous sectors of life in East Germany, the general conditions for spatial mobility in Germany were redefined. Since then the marked migration losses of the new federal states (Länder) and the re-emergence of migrations from the cities to suburban areas have overlapped the continuous shifts of predominant migration linkages that also occur in the west. This article considers the question how internal migrations have developed more than a decade after the unification, which prominent patterns have emerged and in what way a transition from historic reversals towards a new normality has taken place.